A Q-switched erbium-doped fiber laser with a carbon nanotube based saturable absorber - Harun, Sulaiman Wadi; Ismail, M.A.; Ahmad, F.; Ismail, M.F.; Nor, Roslan Md; Zulkepely, N.R.; Ahmad, Harith (2012)
We demonstrate a simple, compact and low cost Q-switched erbium-doped fiber laser (EDFL) using single-wall carbon nanotubes (CNTs) as a saturable absorber for possible applications in metrology, sensing, and medical diagnostics. The EDFL operates at around 1560nm with repetition rates of 16.1 kHz and 6.4 kHz with saturable absorbers SA1 and SA2 at a pump power of 120mW. The absorbers are constructed by optically driven deposition and normal deposition techniques. It is observed that the optical deposition method produces a Q-switched EDFL with a lower threshold of 70mW and better Q-switching performance compared to that of the normal deposition method. The EDFL also has pulse energy of 90.3 nJ and pulse width of 11.6 mu s at 120mW pump power.